Criteria for intensive care unit admission and severity of illness. Issue 4 (April 2015) - Baruch, Miriam; Messer, Ben
Abstract: This article explores the provision and organization of critical care services in the UK and examines the issues surrounding admission to, discharge from and the withholding of critical care. Critical care expansion in the UK in recent years has centred on the provision of increased numbers of beds and the development of outreach services. Despite the expansion in critical care there is difficulty in matching supply and demand for beds. There remains controversy regarding the effectiveness of outreach in improving outcomes for patients referred to critical care. The discharge of patients from critical care has also come under scrutiny since mortality rates are higher for patients discharged out-of-hours. Patients' needs following critical care are carefully planned with the base medical teams because readmission to critical care is associated with increased mortality. Scoring systems are used in critical care to compare outcomes between critical care units and to facilitate research but cannot predict outcome for individual patients. The decision that patients will not benefit from critical care admission can be one of the most difficult. Many patients who would not have been considered for organ support previously are now admitted to critical care with pre-determined limits of treatment. Involvement of the base team is integral to making decisions for these patients.